Biological, Technical, and Financial Feasibilities Study of Spirulina sp. Biomass Production with Modified Commercial Medium in Indonesia - Chessandy Rilisa; Gede Suantika (3BIO: Journal of Biological Science, Technology and Management, 2021)
Spirulina sp. is the most common cyanobacteria commodity used in the bioindustry for functional food, source of protein, bioactive compounds, and biopigment. Production of Spirulina sp. still facing several problems such as high cost of culture medium with the less effective result, especially in developing countries. The medium was modified with commercial chemicals and fertilizers locally available in Indonesia to reduce the production cost. This study aimed to assess the biological, technical, and financial feasibility of Spirulina sp. biomass production using a modified commercial medium. Based on the biological feasibility study, the modified commercial medium (ZK1 and ZK2) gives a similar result to the standard medium, equal for growth rate and protein content. However, the result contains lower fat, carbohydrates, and biopigment. The financial feasibility analysis suggested that the system is feasible starting from 1.2-1.5 kg biomass production in a month. The best result gained on the production capacity of 5 kg biomass using ZK2 medium, with NPV of IDR 183,208,962 (US$12,769), IRR of 73%, B/C ratio of 7.8, and payback period in 7 months. It can be concluded that modified commercial medium was biologically, technically, and financially feasible to be applied in industrial biomass production of Spirulina sp.